Determinação de curcuminoides e avaliação da capacidade antioxidante contra espécies reativas de oxigênio e nitrogênio de extratos de curcuma longa e constituintes isolados - Camatari, Fabiana Oliveira dos Santos (2017)
In biological systems, several metabolic and environmental factors are responsible for the production of reactive oxygen (ROS) and nitrogen (RNS) species. The exacerbated production of these reactive species or the significant decrease in the effectiveness of the defenses against them causes the redox imbalance, with consequent damage to biological macromolecules, which is associated to the emergence and progression of several diseases. Among the exogenous antioxidants, phenolic compounds of plants have been highlighted by their ability to scavenge various reactive species. Among the most studied plants, Curcuma longa has many beneficial properties for health, which are mainly associated with the phenolic compounds present in the rhizome, known as curcuminoids (curcumin, demethoxycurcumin and bisdemethoxycurcumin), but the benefits are more particularly attributed to curcumin. Thus, the objective of this study was to investigate the antioxidant capacity of C. longa extracts and to determine their contents in curcuminoids, investigating the antioxidant action of the extract and of each isolated curcuminoid against ROS and RNS. The identification and quantification of curcuminoids, the total phenols content analysis and the antioxidant capacity in terms of scavenging of the 2,2-diphenyl-1-picryl-hydrazyl radical (DPPH•) and the FRAP method (ferric reducing antioxidant power) were carried out for methanol (CM), defatted methanol (CHM), ethanol (EC) and hexane (CH) extracts, besides commercial extract (ExtFarC) of C. longa. The elimination capacity of ROS and RNS was performed for CE and isolated curcuminoids (curcumin, demethoxycurcumin and bisdemethoxycurcumin). The CM, CHM and CE had shown the three curcuminoids in their compositions, while, for the ExtFarC, curcumin was the predominant compound. The CE and ExtFarC had shown the higher total phenols content and antioxidant activity by the FRAP method, besides the lower IC50 values for to the DPPH• radical. The use of high performance liquid chromatography (HPLC) with spectrophotometric detection (DPPH•-HPLC-UV) indicated that curcumin and demethoxycurcumin had the greater potential for capture of DPPH•, as observed by the reduction of their peaks in HPLC, at equivalent contact time. In the experiments related to hypochlorous acid (HOCl), nitric oxide (•NO) and peroxynitrite (ONOO‾), the curcuminoids had shown a direct efficiency toward their elimination, similarly to the positive control (quercetin). For CE, despite showing higher IC50 values against these species, in comparison to the isolated compounds, it presented lower IC50 values, when compared to other plants’ extracts, studied by the same methods. Although curcumin is the target of many therapeutic studies for a number of diseases, the present data show that the three curcuminoids can play essential roles against ROS and RNS, and thus, may be considered promising in the prevention and treatment of diseases related to oxidative stress.